La poésie féminine victorienne ou comment donner un sexe aux anges ? - Fabienne Moine Perez (Cahiers Victoriens et Edouardiens)
Although women had to fit a specific social position that they had been allocated in the middle of the 19th century, women poets resexualized the angelic figure of the woman as they chose to reveal sexual pleasure through writing about lesbian relationships. Even if it was almost impossible to indulge in sensuous pleasure during the Victorian era, some female poets (Elizabeth Barrett Browning, Christina Rossetti, Amy Levy or Michael Field...) were forced to break with innocent poetry and to discover sexual pleasure throughout poems tackling lesbian questions. Legendary women such as Xanthippe or Sappho became key figures for women poets. Such role models allowed female poets to sexualize women without calling in male sexuality. Sexual pleasure as unveiled by 19th century-female poets is nevertheless smothered through writing lesbian poetry which paradoxically suggests the denial of any explicit sexuality. Finally, if these women tried to insist on a sexual identity through poetry, they were also given the opportunity to reach a literary identity.